Interleukin (IL)‐31 activates signal transducer and activator of transcription (STAT)‐1, STAT‐5 and extracellular signal‐regulated kinase 1/2 and down‐regulates IL‐12p40 production in activated human macrophages. Issue 6 (27th April 2013) - Kasraie, S.; Niebuhr, M.; Werfel, T.
Abstract Background Interleukin‐31 is a cytokine expressed by activated T cells. A major function of IL‐31 in atopic dermatitis (AD) is the induction of pruritus in the skin. We recently showed that IL‐31 induces pro‐inflammatory cytokines following staphylococcal exotoxins' stimulation in human macrophages. However, signalling pathways of IL‐31 in activated human macrophages still remain unclear. The aim of the study was to investigate the signalling pathways of IL‐31 receptor as well as functional effects of IL‐31 in activated macrophages. Methods Human macrophages were prestimulated with staphylococcal exotoxins (SEB, α‐toxin) to up‐regulate the IL‐31 receptor with and without IL‐31. Phospho‐signal transducer and activator of transcription (pSTAT) 1/3/5, phospho‐extracellular signal‐regulated kinase (ERK 1/2), β‐actin as well as p21/WAF/Cip1 levels were determined by means of Western blot analysis. Interleukin‐12p40, IL‐12p70 and IL‐23 secretions were assessed by using an enzyme‐linked immunosorbent assay. Results Interleukin‐31 strongly activated STAT‐1 and 5 but not STAT‐3 in human macrophages after up‐regulation of IL‐31 receptor with staphylococcal exotoxins. p21/WAF/Cip1 expression was induced by IL‐31 in activated human macrophages. Furthermore, IL‐31 down‐regulated. IL‐12p40 secretion via ERK 1/2 phosphorylation in human macrophages following up‐regulation of IL‐31 receptor with staphylococcal exotoxins. Conclusions The T helper (Th) 2 cytokine IL‐31 induces pro‐inflammatory effects in activated human macrophages via STAT‐1 and 5 phosphorylation. Interleukin‐31‐induced ERK 1/2 activation contributes to the underlying mechanism of Th1 cytokine IL‐12 suppression in macrophages. This mechanism may be relevant in Th2 inflammatory responses and may help to develop therapeutic strategies in IL‐31‐associated diseases such as AD.